KEPUASAN KERJA SEBAGAI MEDIASI HUBUNGAN ANTARA PERSONALITY DAN KINERJA KARYAWAN - Rajak, Adnan; Taslim, Fadli Ali (Jurnal MS, 2020)
Objective: The purpose of this study are: (1) Knowing and analyzing the influence of personality on employee performance at SMEs in Ternate City; (2) Knowing and analyzing the effect of job satisfaction on employee performance at SMEs in Ternate City; (3) Knowing and analyzing the influence of personality on employee job satisfaction at SMEs in Ternate City; and (4) Knowing and analyzing job satisfaction is able to mediate the influence of personality on employee performance at SMEs in Ternate City. In addition, the results of this study are expected to provide the following benefits: Theoretical Benefits: To support and enrich the development of human resource management (HRM). Methodology: The test equipment used is Structural Equation Modeling (SEM) using Smart PLS as a statistical test tool. Finding: H1 H2, and H3 are accepted at the 5% confidence level Conclusion: The results showed that: (1) Personality had a positive and significant effect on employee job satisfaction at SMEs in Ternate City; (2) Personality (personality) has no significant effect on employee performance at SMEs in Ternate City: (3) Job satisfaction has a positive and significant effect on employee performance at SMEs in Ternate City; and (4) job satisfaction is able to fully mediate the influence between personality and employee performance.